Promiscuous, Multi-Target Lupane-Type Triterpenoids Inhibits Wild Type and Drug Resistant HIV-1 Replication Through the Interference With Several Targets - Bedoya, Luis M.; Beltrán, Manuela; García-Pérez, Javier; Obregón-Calderón, Patricia; Callies, Oliver; Jímenez, Ignacio A.; Bazzocchi, Isabel L.; Alcamí, José (Frontiers in Pharmacology, 2018)
Current research on antiretroviral therapy is mainly focused in the development of new formulations or combinations of drugs belonging to already known targets. However, HIV-1 infection is not cured by current therapy and thus, new approaches are needed. Bevirimat was developed by chemical modification of betulinic acid, a lupane-type pentacyclic triterpenoid (LPT), as a first-in-class HIV-1 maturation inhibitor. However, in clinical trials, bevirimat showed less activity than expected because of the presence of a natural mutation in Gag protein that conferred resistance to a high proportion of HIV-1 strains. In this work, three HIV-1 inhibitors selected from a set of previously screened LPTs were investigated for their targets in the HIV-1 replication cycle, including their maturation inhibitor effect. LPTs were found to inhibit HIV-1 infection acting as promiscuous compounds with several targets in the HIV-1 replication cycle. LPT12 inhibited HIV-1 infection mainly through reverse transcription, integration, viral transcription, viral proteins (Gag) production and maturation inhibition. LPT38 did it through integration, viral transcription or Gag production inhibition and finally, LPT42 inhibited reverse transcription, viral transcription or Gag production. The three LPTs inhibited HIV-1 infection of human primary lymphocytes and infections with protease inhibitors and bevirimat resistant HIV-1 variants with similar values of IC50. Therefore, we show that the LPTs tested inhibited HIV-1 infection through acting on different targets depending on their chemical structure and the activities of the different LPTs vary with slight structural alterations. For example, of the three LPTs under study, we found that only LPT12 inhibited infectivity of newly-formed viral particles, suggesting a direct action on the maturation process. Thus, the multi-target behavior gives a potential advantage to these compounds since HIV-1 resistance can be overcome by modulating more than one target.